2022
DOI: 10.31586/ojp.2022.395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stress on the Job Performance of Psychiatric Nurses

Abstract: The purpose of this study was to examine the effects of stress on the job performance of psychiatric nurses in the Ankaful Psychiatric Hospital in Cape Coast. A descriptive survey design was adopted for the study. A sample of 150 psychiatric nurses were selected from a population of 197 psychiatric nurses using a simple random sampling procedure. Data were collected using the Weiman Occupational Stress Scale (WOSS) questionnaire. 143 answered questionnaires were retrieved out of the 150 questionnaires offered,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…Likewise, seniority or length of service positively improves psychiatric nurses' performance. Fia et al (2022), in a study, revealed that the performance of psychiatric nurses is negatively affected due to the effects of stress, which include mild to severe headaches, loss of concentration, fatigue, anger, overreaction, looking for excuses, and absence from work, and forgetfulness. Furthermore, Matsumoto and Yoshioka (2019)found that the psychological condition of psychiatricnurses could affect their performance in nursing care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, seniority or length of service positively improves psychiatric nurses' performance. Fia et al (2022), in a study, revealed that the performance of psychiatric nurses is negatively affected due to the effects of stress, which include mild to severe headaches, loss of concentration, fatigue, anger, overreaction, looking for excuses, and absence from work, and forgetfulness. Furthermore, Matsumoto and Yoshioka (2019)found that the psychological condition of psychiatricnurses could affect their performance in nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Fia et al (2022) concluded that there is a significant and negative relationship between work stress and performance. When mental care workers experience stress, patients with mental disorders who are treated also receive the impact.…”
Section: Discussionmentioning
confidence: 99%
“…Table (8) shows that a highly significant model with a p value of.000 was found using the f test (10.713). R2 = 0.48 indicates that 48% of the variation in workplace well-being can be explained by this.…”
Section: Figure (3)mentioning
confidence: 99%
“…Psychiatric nursing is a widely highstressful profession, according to numerous studies, and this is a worldwide problem. (6,7,8) The profession is emotionally and physically stressful, and burnout is common. (9,10) Insufficient job training to handle this complex patient population, interpersonal conflicts with coworkers, bullying at work, and demanding relationships with patients and relatives are some of the major sources of workplace stressors for nurses.…”
Section: Introductionmentioning
confidence: 99%